1991
DOI: 10.1111/j.1365-2265.1991.tb00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological and biochemical distinctiveness of atypical aldosterone‐producing adenomas responsive to upright posture and angiotensin

Abstract: Fifteen patients with primary aldosteronism were classified as angiotensin II-unresponsive aldosterone-producing adenoma (AII-U APA, n = 9), or angiotensin II-responsive aldosterone-producing adenoma (AII-R APA, n = 6), based on the responsiveness of aldosterone to upright posture and to angiotensin II infusion. Lack of aldosterone response to angiotensin II infusion immediately postoperatively in the AII-R APA subtype was consistent with previous responsiveness residing solely within the adenoma. Cortisol lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 28 publications
4
37
2
Order By: Relevance
“…Several studies have shown distinct biochemical characteristics of patients with primary aldosteronism due to APA, based on different aldosterone responses to upright posture (7, 29 -31) and dexamethasone administration (12, 13, 32 -34). Responsiveness to endogenous angiotensin II and ACTH inhibition may reflect a different prevalence of zona fasciculata-like cells within the tumor (30,35). No relationship was found in our patients with APA between CYP11B1 and CYP11B2 transcript levels and aldosterone secretion, either basal or in response to dynamic testing.…”
Section: Discussionmentioning
confidence: 43%
“…Several studies have shown distinct biochemical characteristics of patients with primary aldosteronism due to APA, based on different aldosterone responses to upright posture (7, 29 -31) and dexamethasone administration (12, 13, 32 -34). Responsiveness to endogenous angiotensin II and ACTH inhibition may reflect a different prevalence of zona fasciculata-like cells within the tumor (30,35). No relationship was found in our patients with APA between CYP11B1 and CYP11B2 transcript levels and aldosterone secretion, either basal or in response to dynamic testing.…”
Section: Discussionmentioning
confidence: 43%
“…Another possibility is that APAis composed of both aldosterone-producing cells and cortisol-producing cells. The reports describing the APAcontaining zona glomerulosa, zona fasciculate and their hybrid cells (9,18,19) support this possibility. In our case, the latter possibility is more likely considering the result of immunohistochemical studies.…”
Section: Discussionsupporting
confidence: 48%
“…It was subsequently shown that this lack of response to posture or the infusion of angiotensin (Ang) II was not shared by all of the APAs and appeared restricted to those with ZF morphology and the production of excessive "hybrid" steroids18-hydroxyand 18-oxo-cortisol. 9,10 This makes our observation that our APAs with mutations lacked an aldosterone response to posture all the more intriguing, because it represents the response of the APA cells to Ang II generated in vivo by the renin-Ang system on standing. 9,10,24 Possibly, APA cells depolarized by KCNJ5 mutations cannot respond to Ang II receptor activation by further depolarization and aldosterone release.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 This makes our observation that our APAs with mutations lacked an aldosterone response to posture all the more intriguing, because it represents the response of the APA cells to Ang II generated in vivo by the renin-Ang system on standing. 9,10,24 Possibly, APA cells depolarized by KCNJ5 mutations cannot respond to Ang II receptor activation by further depolarization and aldosterone release. Alternatively, the histology of APAs that are unresponsive to posture and secrete excess amounts of the hybrid 18-oxo steroids may be relevant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation